The Future of Health Technology: Analyzing User-Based Design in the Electronic Growth Chart Interface - Muna, Niyalatul; Mudiono, Demiawan Rachmatta Putro; Nurmawati, Ida; Wicaksono, Andri Permana; Muflihatin, Indah; Navalani, Faradita (P3M Politeknik Negeri Jember, 2025)
Electronic Growth Chart (e-KMS) is an innovative platform for monitoring children's health by tracking weight and height. The user interface (UI) is designed for intuitive interaction, allowing users to operate the system efficiently. This research aims to analyses the e-KMS UI based on established UI standards using a descriptive quantitative method with a User-Centered Design (UCD) approach. The study involved 15 respondents. Results showed that the system was very easy to use and essential for monitoring children's health. Consistency was evaluated across different devices, revealing that the system functioned uniformly. Feedback was analyses by examining the system's visual cues during key actions such as logging in and inputting a child’s data, ensuring users could confirm successful operations. Finally, Visibility was assessed by observing how well users understood the input results, with the system effectively displaying a child’s growth chart. The findings highlight the importance of these four UI principles in creating a user-friendly, aesthetically pleasing, and intuitive interface. By adhering to these principles, the e-KMS UI enhances user engagement, satisfaction, and overall user experience, contributing to more effective health monitoring for children. To enhance usability, future improvements should focus on accessibility, streamlined navigation, and user feedback integration.